Analsis Perbandingan Return Saham Di Masa Covid-19 Pada Perusahaan Perbankan Syariah Yang Terdaftar Di Bursa Efek Indonesia dan Bursa Malaysia - Dean Fanni Yolanda; Zul Azmi; Dwi Fionasari (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
This study aims to analyze the comparison of stock returns during the Covid-19 period in Islamic banking companies listed on the Indonesian stock exchange and the Malaysian stock exchange. This research is a quantitative research using secondary data. The research data is in the form of stock prices at the closing price obtained from two exchanges, namely the Indonesia Stock Exchange and the Malaysia Stock Exchange for the 2020-2021 period. The results of the research based on the normality test using the Kolmogorov-Smirnov test tool show that the p-value is 0.000 <0.05, which means that the data is not normally distributed. The results of hypothesis testing using the Mann Whitney test tool show a significance of 0.000 for stock returns during the Covid-19 period in Islamic banking companies listed on the Indonesia Stock Exchange and Malaysia Stock Exchange. This shows a p value <0.05. Thus it means that Ha is accepted, because from the data it is said that there are differences in stock returns during the Covid-19 period for Islamic banking companies listed on the Indonesia Stock Exchange and the Malaysia Stock Exchange.